Effect of fasting on the urinary excretion of nitrogen and purine derivatives by Zebu (Bos indicus) and crossbred (Bos indicus X Bos taurus) cattle - Osuji, P.O.; Nsahlai, I.V.; Khalili, H. (Informa UK Limited, 1996)
Six cattle (3 Boran (Bos indicus) and 3 crossbred (Bos indicus X Bos taurus) were fasted for 20 days to estimate the effect of fasting on the excretion of nitrogen (N) and purine derivatives (PD) in the urine. PD excretion (y) for each genotype was related to time (t in days) by means of an exponential model: Y=A+Be -kt where A is the endogenous excretion, k the fractional rate of excretion of exogenous PD B. The equations relating y to time (t) were: y=0.172+0.178e -.392t, R to the square root of 2=0.86; and y=0.108 + 0.146e -0.108t, R to the square root of 2=0.61 for the Zebu and crossbred cattle, respectively. The daily fasting urinary nitrogen (N g/kg W 0.75) was related to total daily PD excretion (y mmol/kg W 0.75) by the equations: y = 0.00294 + 0.7285 plus or minus 0.136 N, Adj R to th square root of 2 = 0.75 (crosses). y=0.01099 + 0.9229 plus or minus 0.090 N, Adj R to the square root of 2 = 0.92 (Zebu). The intercepts for both equations were not different from zero (P>0.05). The endogenous PD excretion (mmols/kg W 0.75) of the Zebu (0.172) was about 1.59 times that of the crossbred (0.108) cattle. The fractional rate of excretion of exogenous PD of the Zebu was 3.6 times that of the cross bred. The ratios of allantoin to total PD, uric acid to allantoin and uric acid to PD did not change with time (P>0.05) but differed (P<0.01) between genotypes. The present results support the hypothesis that Bos indicus cattle and their crosses may have different fasting nitrogen metabolism from their Bos taurus counterparts. Based on these results we suggest endogenous PD values of 0.172 and 0.108 mmol/kg W 0.75 for Zebu and crossbred cattle, respectively.